Observations of microphysical properties and radiative effects of a contrail cirrus outbreak over the North Atlantic - Wang, Ziming; Bugliaro, Luca; Jurkat-Witschas, Tina; Heller, Romy; Burkhardt, Ulrike; Ziereis, Helmut; Dekoutsidis, Georgios; Wirth, Martin; Groß, Silke; Kirschler, Simon; Kaufmann, Stefan; Voigt, Christiane (Atmospheric Chemistry and Physics, 2023)
Contrail cirrus constitute the largest radiative forcing (RF) component to the total aviation effect on climate. However, the microphysical properties and radiative effects of contrail cirrus and natural cirrus clouds in the same meteorological conditions are still not completely resolved. Motivated by these uncertainties, we investigate an extended cirrus region perturbed by aviation in the North Atlantic region (NAR) on 26 March 2014 during the Midlatitude Cirrus (ML-CIRRUS) experiment. On that day, high air traffic density in the NAR combined with large scale cold and humid ambient conditions favored the formation of a contrail cirrus outbreak situation. In addition, low coverage by low-level water clouds and the homogeneous oceanic albedo increased the sensitivity for retrieving cirrus properties and their radiative effect from satellite remote sensing. This allowed us to extend the current knowledge on contrail cirrus by combining airborne in situ, lidar and satellite observations. In the synoptic context of a ridge cirrus, an extended thin ice cloud with many persistent contrails and contrail cirrus has been observed for many hours with the geostationary Meteosat Second Generation (MSG)/Spinning Enhanced Visible and InfraRed Imager (SEVIRI) from the early morning hours until dissipation after noon. Airborne lidar observations aboard the German High Altitude and LOng Range Research Aircraft (HALO) suggest that this cirrus has a significant anthropogenic contribution from aviation. A new method based on in situ measurements was used to distinguish between contrails, contrail cirrus and natural cirrus based on ice number and gas phase NO concentrations. Results show that contrail effective radii ( R eff ) reach at most 11 µ m, while contrail cirrus R eff can be as large as 51 µ m. Contrail and contrail cirrus mean R eff is 18 % smaller than that of natural cirrus. We find that a difference in R eff between contrail cirrus and natural cirrus survives in this contrail cirrus outbreak event. As for radiative ...